Stunting Prevention Policy as a Form of Child Health Rights Legal Protection - Hartotok, Hartotok; Absori, Absori; Dimyati, Khudzaifah; Santoso, Heru; Budiono, Arief (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The objectives of this research are to reveal and to analyze the stunting prevention policy as a form of legal protection for children’s health rights (HR). METHODS: This type of research is a normative legal research approach to the legislation approach and conceptual approach. RESULTS: The results of the study show that stunting prevention policy as a form of legal protection for child HR has not been able to reduce the number of stunting. The high prevalence of stunting as evidence of the government’s failure in legal protection against the problem of malnutrition. Ignoring children’s rights is a form of HR violations committed by the state. CONCLUSION: Need to regulate the law related to stunting as a manifestation of state responsibility in upholding children’s rights. Prevention and handling of stunting are carried out holistically in various sectors with commitment and synergy between the central/regional government, parents, family, and community.